CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND ISLAMIC BANK PROFITABILITY (EVIDENCE FROM INDONESIA) - Nugraha, Tsamara Hasanah; Faturohman, Taufik (Journal of Business and Management, 2018)
Abstract. By  doing  this  research,  the  author  wants  to   examine  the  relationship  between corporate social responsibility (CSR) disclosure and profitability  in Islamic banks in Indonesia over the period of 2008-2017. The author tried to explore whether CSR and its individual dimension   index   would   have   significant   relationship   with   financial   performance   using profitability ratio (ROA), since it has inconsistencies results, theoretical explanation suggests a possibly positive, negative, or neutral relationship between two coefficients. A content analysis method is conducted to measuring the CSR disclosure. Panel data regression were applied to analyse the relationship between independent and dependent variables, since it’s a combination of time-series and cross-sectional data. Based on the data from the sample of 102 Islamic bank annual reports, corporate social responsibility disclosure gives a significant positive relationship with profitability in Indonesia Islamic banks. The individual dimension of CSR namely ‘mission and vision, ‘product and services’, and ‘commitment toward employees’ also found to have a positive significant relationship. Keyword: CSR disclosure, Profitability, Islamic Bank